Draft Annual Plan 1986-87 Vol. IV (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1985)
At the end of Seventh Five Year Plan 1985-90 the projected population of 6-11 years age group children is likely to be 17.94 Lakhs. the enrolment figures at the end of 1984-85 was anticipated at 15.10 Lakhs (actual 15.26 Lakhs).
Planning Department, Government of Haryana